2008
DOI: 10.1007/s00244-007-9077-2
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides: Blood Cholinesterase Activity in a Farming Community in Ghana

Abstract: A survey was undertaken to establish the extent of pesticide exposure in a farming community. Cholinesterase (ChE) activity in whole blood was used as a marker for assessing exposure to pesticides. Complete data were gathered for 63 farmers at Akumadan (exposed) and 58 control subjects at Tono, both prominent vegetable-farming communities in Ghana, by means of a questionnaire and blood cholinesterase analyses (acetylcholine assay). Although whole-blood ChE was significantly lower in the exposed than the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 15 publications
2
14
0
6
Order By: Relevance
“…Most other studies of pesticide exposure have used a study design with nonexposed controls (e.g., Cataño et al 2008; Ntow et al 2009; Rendón von Osten et al 2004) or a pre–post design (Gamlin et al 2007; Thetkathuek et al 2005) to identify cholinesterase depression. Such designs are not always practical with migrant workers in the eastern United States.…”
Section: Discussionmentioning
confidence: 99%
“…Most other studies of pesticide exposure have used a study design with nonexposed controls (e.g., Cataño et al 2008; Ntow et al 2009; Rendón von Osten et al 2004) or a pre–post design (Gamlin et al 2007; Thetkathuek et al 2005) to identify cholinesterase depression. Such designs are not always practical with migrant workers in the eastern United States.…”
Section: Discussionmentioning
confidence: 99%
“…Risks from pesticide use in vegetable production for farmers and consumers have been confirmed by Ntow et al (2009) and Amoah et al (2006). In contrast to the use of polluted water, farmers were generally aware that pesticides are hazardous ) although there were slight differences in farmers' and experts' perception of the relative hazard of using the WHO ranking as reference.…”
Section: Difference Between Perceived and Measured Risksmentioning
confidence: 97%
“…Akumadan is known to be a highly contaminated site with pesticides, including anticholinesterase substances [23]. Use of pesticides such as carbofuran (a carbamate pesticide under the trade name Furadan 3G) and chlorpyrifos (an organophosphate pesticide under the trade name Durban 4E) in the study area has been reported [16,31]. Carbofuran and chlorpyrifos are anti-ChE pesticides [48,49] and we therefore speculate that carbofuran and chlorpyrifos are among the pesticides responsible for blood ChE inhibition at Akumadan.…”
Section: Discussionmentioning
confidence: 93%
“…For the comparison of symptoms according to exposure, we used the odds ratio for the prevalence as a measure of association. A level of probability below 0.05 was considered statistically significant for all analysis [31].…”
Section: Discussionmentioning
confidence: 99%